KAJIAN SIFAT FISIK, KIMIA DAN SENSORIS CRACKERS SUBSTITUSI TEPUNG SUKUN (Artocarpus communis) TERMODIFIKASI ASAM ASETAT DENGAN PENAMBAHAN SARI DAUN PANDAN WANGI (Pandanus amaryllifolius) - Astuti, Dwi; Kawiji, Kawiji; Nurhartadi, Edhi (Jurnal Teknologi Hasil Pertanian, 2018)
The purpose of this research was to determine the effect of substitution of acetic acid modified breadfruit flour with the addition of pandan leaves extract against physic, chemical and sensory characteristic of crackers and determine their antioxidant activity on crackers. This study uses a Completely Randomized Design (CRD) with one factor substitution of acetic acid modified breadfruit flour. Sensory data were analyzed by one-way ANOVA, if there is a difference it was followed with significance test using Duncan’s Multiple Range Test (DMRT) at significance level of 0,05. The results showed that substitution of acetic acid modified breadfruit flour did not significantly affect the physical characteristic (hardness), chemical characteristics such as moisture content, ash, protein, carbohydrate and antioxidant activity of crackers. However, the substitution of acetic acid modified breadfruit flour affected the levels of fat, crude fiber, sensory characteristics (colour, flavor, taste, texture and overall) of crackers. The antioxidant activity of crackers is about 3.27%-4.16%.